The Elman-Lam-Krüskemper Theorem. (28th June 2011) - Becher, Karim Johannes; Leep, David B.
Abstract : For a (formally) real fieldK, the vanishing of a certain power of the fundamental ideal in the Witt ring ofK ( - 1 ) implies that the same power of the fundamental ideal in the Witt ring ofK is torsion free. The proof of this statement involves a fact on the structure of the torsion part of powers of the fundamental ideal in the Witt ring ofK . This fact is very difficult to prove in general, but has an elementary proof under an assumption on the stability index ofK . We present an exposition of these results.